Maternal nutrition, fetal growth, and cardiovascular risk in Filipino adolescents - Kuzawa, Christopher William (ProQuest Dissertations & Theses, 2001)
This dissertation test the hypothesis that poor fetal nutrition during pregnancy elevates risk for cardiovascular disease, as indicated by cholesterol profiles measured in adolescence. Birth outcomes (birth weight, length, and relative weight) and maternal nutritional status and diet during pregnancy are used individually, and in combination, as indices of fetal nutritional sufficiency. Subjects for this research include 608 Filipino adolescents (15–16 years) participating in the Cebu Longitudinal Health and Nutrition Survey, a one-year birth cohort study begun in 1983–84. Mothers were enrolled in the study during the third trimester of pregnancy, at which time information on maternal diet, nutritional status, and socioeconomic factors were collected. Follow-ups were conducted at birth, during infancy, childhood, and adolescence, providing a lifetime of information on the diet, activity level, socio-economic status, and growth of each participant. This research develops a novel model of fetal nutritional sufficiency that incorporates variation in both fetal growth potential (a marker for fetal demand for nutrients) and maternal nutritional supply. Four categories hypothesized to indicate the likelihood of fetal nutritional insufficiency are created, using combinations of high/low maternal stature (proxy of fetal growth potential and thus demand for nutrients) and high/low 3rd trimester arm fat area (maternal nutritional supply). These categories successfully predict CVD risk in male but not female offspring. Males categorized as high risk for prenatal energy shortfall have highest mean CVD risk for 5 of 6 lipids investigated, while those categorized as low risk for energy shortfall have lowest risk for all lipids. Collectively, the multiple measures of maternal nutritional status, diet, and fetal growth used in this study provide some of the strongest evidence to date that prenatal undernutrition heightens risk for diseases of overnutrition later in life, and suggest that what a mother eats during pregnancy has lasting influence on the lipid profiles and cardiovascular health of her offspring. These relationships are already strong during adolescence in a population with low intake of dietary fat and low occurrence of obesity, and will likely be strengthened if obesity rates continue to rise in Cebu. The finding that relationships between prenatal factors and lipids are stronger and more consistent among males provides a rationale to investigate the role of sex steroids in lipid metabolism programming. (Abstract shortened by UMI.)